Wpływ zlodowacenia warty na architekturę osadów czwartorzędowych wokół zbiornika wodnego Jeziorsko = Warta glaciation influence on architecture of the quaternary deposits around the Jeziorsko reservoir - Widera, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Quaternary deposits in the Jeziorsko reservoir vicinity are more strongly disturbed glacitectonically than they thought earlier. Numerous faults, thrusts and folds were documented, but the last on es were only discussed in detail in this article. The greatest deformations were caused by the Warta ice sheet, which was the youngest one in the study area.
Keywords: glacitektonika; zlodowacenie warty; zbiornik Jeziorsko; glacitectonics; Warta glaciation; Jeziorsko reservoir